Development and Reliability Testing of a Patient Education Performance Tool for Physical Therapy Students. Issue 1 (March 2019) - Forbes, Roma; Mandrusiak, Allison
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Purpose: While patient education is an expected competency for physical therapy graduates, no instrument is available for assessing student performance of patient education. The objective of this study was to report on the development of a physical therapy patient education (PTPE) performance tool and to examine its internal consistency, interrater and test–retest reliability. Methods: Items for the PTPE performance tool were generated from a previous study using expert consensus. To measure interrater reliability, 3 independent assessors used the tool to examine 45 physical therapy students' performance of patient education in an objective standardized clinical examination (OSCE; video-recorded). To measure test–retest reliability, the tool was applied twice with an interval of 16 days. To measure internal consistency, the tool was used to assess 164 video-recorded student OSCE performances. Outcomes: Panel agreement on the PTPE performance tool was achieved. Interrater reliability of the individual assessment items ranged from 0.57 (item 5) to 0.89 (item 1). The overall test–retest reliability for the tool was 0.76. Individual items ranged from 0.61 (item 5) to 0.86 (item 7). The overall internal consistency was 0.81, indicating acceptable agreement. Discussion and Conclusion: The PTPE performance tool demonstrates acceptable reliability and internal consistency as an assessment tool for student performance of patient education. The results warrant further investigation of the PTPE in wider student, clinical and professional settings.